Density functional theory study of elemental mercury adsorption on boron doped graphene surface decorated by transition metals - Jungsuttiwong S. (2017)
First principle calculations were performed to study the adsorption of Hg on a transition metal(TM) decorated boron-doped graphene (BDG) surface. The study focused on six possible sites of TM atom on BDG surface to obtain the most stable site which has been used to find the most stable site for TM cluster on BDG surface, finally the adsorption of Hg 0 on a BDG surface decorated with TM atom and clusters were investigated. Geometric and electronic aspects of structures were investigated by density functional theory (DFT) using the DMol software package in Materials Studio 5.5. The main calculations were performed using the generalized gradient approximation with a PW91 functional. As a TM cluster, the Pd 4 type A structure shows the highest Hg adsorption performance. The Pd 4 -BDG adduct adsorbs a single Hg atom with adsorption energy of -0.97 eV. In-depth PDOS analysis suggested that the interaction of Hg-5d orbitals and Pd-4d, Pt-5d orbitals contribute to its high adsorption strength. Furthermore, the capacity studies of Hg adsorption on Pd 4 decorated BDG suggested that six Hg atoms could adsorb stably on the surface.